2015
DOI: 10.1007/s00127-015-1094-2
|View full text |Cite|
|
Sign up to set email alerts
|

One-year incidence and prevalence of seclusion: Dutch findings in an international perspective

Abstract: Gathering comprehensive data allows comparisons between countries, increasing our understanding of the impact of different cultures, legislation and health care systems on coercion. In the Netherlands, seclusion is still the main type of coercion, despite significant improvements in the last few years. It is shorter when applied in combination with enforced medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 59 publications
2
60
1
10
Order By: Relevance
“…In contrast to other large studies (Keski-Valkama et al 2010;Noorthoorn et al 2015), patient diagnosis was largely unrelated to either PICU transfer or seclusion with the exception that patients with bipolar disorder were twice as likely to be transferred to PICU compared with patients with schizophrenia. The fact that we adjusted for behaviours and traits commonly associated with this diagnosis (i.e., manic, agitated, demanding and irritable behaviour), implies that bipolar disorder patients may present with other behaviours which cause them to be viewed by clinical staff as needing PICU treatment.…”
Section: Demographic and Clinical Predictors Of Treatmentcontrasting
confidence: 73%
“…In contrast to other large studies (Keski-Valkama et al 2010;Noorthoorn et al 2015), patient diagnosis was largely unrelated to either PICU transfer or seclusion with the exception that patients with bipolar disorder were twice as likely to be transferred to PICU compared with patients with schizophrenia. The fact that we adjusted for behaviours and traits commonly associated with this diagnosis (i.e., manic, agitated, demanding and irritable behaviour), implies that bipolar disorder patients may present with other behaviours which cause them to be viewed by clinical staff as needing PICU treatment.…”
Section: Demographic and Clinical Predictors Of Treatmentcontrasting
confidence: 73%
“…In an international study comparing factors associated with the use of the three main coercive measures seclusion, restraint, and enforced medication (McLaughlin et al 2016)it was found that seclusion was associated with a longer admission duration, regardless of the severity of symptoms at admission. This finding is in line with nationwide Dutch data, also suggesting that the added use of enforced medication could substantially reduce seclusion duration (Noorthoorn et al 2015) and restraint overall (Verlinde et al 2017).…”
Section: Risk Factors Associated With Seclusionsupporting
confidence: 89%
“…This finding is in line with nationwide Dutch data, also suggesting that the added use of enforced medication could substantially reduce seclusion duration (Noorthoorn et al . ) and restraint overall (Verlinde et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…It is debatable to what extent these measures contribute to the reduction of the incidence of aggressive acts. Noorthoorn et al (2015) found positive effects on the duration -not the frequency -of specific coercive measures in psychiatry. A study in British mental health care institutions did not show a reduction in aggressive incidents after staff training programs (Bowers et al, 2006).…”
Section: Aim Of This Studymentioning
confidence: 90%
“…In the past decade, the aims of research on aggressive incidents in mental health care institutions have largely been limited to reducing the use of coercive measures (Noorthoorn et al, 2015;Vruwink et al, 2012;Steinert et al, 2010;Raboch et al, 2010;Bowers et al, 2006).…”
Section: Aggressive Incidentsmentioning
confidence: 99%